Design and Implementation of a Secure Data Exchange System for Government Institutions Using AES, RSA, and TLS (Comprehensive Journal of Science, 2026)
The rapid expansion of digital networks within government institutions has significantly increased the volume of sensitive data exchanged between distributed branches, thereby amplifying exposure to cybersecurity threats such as interception, manipulation, and impersonation attacks. Ensuring confidentiality, integrity, and authentication during data exchange has become a critical challenge. This paper presents the design and implementation of a secure data exchange system tailored for government institutions, based on the integration of Advanced Encryption Standard (AES), Rivest-Shamir-Adleman (RSA), and Transport Layer Security (TLS). The proposed system adopts a hybrid encryption approach, utilizing AES for efficient data encryption, RSA for secure key exchange and digital authentication, and TLS to establish a protected communication channel. The system is implemented using the Python programming language and evaluated through practical experiments measuring encryption performance, resource consumption, and resistance to common network attacks. Experimental results demonstrate that the proposed framework achieves a high level of security while maintaining acceptable performance, making it suitable for real-world deployment in governmental environments.
Keywords: Secure data exchange, Cryptography, AES, RSA, TLS, Government systems, Python